International volunteerism and global responsibility - Badlani, Gopal (Translational Andrology and Urology, 2017)
To review the current status of volunteerism in the field of urology as a global responsibility, a PubMed search was done with keywords: international volunteer, urology, global health, international resident education. Furthermore, internet search using Google and Bing as search engines for the same key words was done. Websites of multinational urological organizations was researched for available information. Expert opinions of key individuals in the arena were obtained. There is a paucity of published literature as to the efforts and outcomes of volunteerism in Urology; most of the information is related to the fistula repair outcomes in medical literature. There is credible information on the impact on resident training in the field of dentistry, general surgery, orthopedics and plastic surgery. The desire to volunteer is demonstrated in a survey of urologists, the delivery of volunteer missions is fragmented, the outcomes or impact of these efforts is less well documented. There is a need to create pathways to harness the desire of urologists to volunteer. Simultaneously, the effort to establish ethical standards and guidelines for surgical care in LMIC countries by visiting doctors is important. There is a tremendous opportunity for resident education in this arena, as demonstrated by the ACGME approved path in general surgery.